Nano-sized Mo- and Nb-doped TiO2 as anode materials for high energy and high power hybrid Li-ion capacitors. (19th April 2017) - Bauer, Dustin; Roberts, Alexander J; Matsumi, Noriyoshi; Darr, Jawwad A
Abstract: Nano-sized Mo-doped titania (Mo0.1 Ti0.9 O2 ) and Nb-doped titania (Nb0.25 Ti0.75 O2 ) were directly synthesized via a continuous hydrothermal flow synthesis process. Materials characterization was conducted using physical techniques such as transmission electron microscopy, powder x-ray diffraction, x-ray photoelectron spectroscopy, Brunauer–Emmett–Teller specific surface area measurements and energy dispersive x-ray spectroscopy. Hybrid Li-ion supercapacitors were made with either a Mo-doped or Nb-doped TiO2 negative electrode material and an activated carbon (AC) positive electrode. Cells were evaluated using electrochemical testing (cyclic voltammetry, constant charge discharge cycling). The hybrid Li-ion capacitors showed good energy densities at moderate power densities. When cycled in the potential window 0.5–3.0 V, the Mo0.1 Ti0.9 O2 /AC hybrid supercapacitor showed the highest energy densities of 51 Wh kg −1 at a power of 180 W kg −1 with energy densities rapidly declining with increasing applied specific current. In comparison, the Nb0.25 Ti0.75 O2 /AC hybrid supercapacitor maintained its energy density of 45 Wh kg −1 at 180 W kg −1 better, showing 36 Wh g −1 at 3200 W kg −1, which is a very promising mix of high energy and power densities. Reducing the voltage window to the range 1.0–3.0 V led to an increase in power density, with the Mo0.1 Ti0.9 O2 /AC hybrid supercapacitor giving energy densities of 12 Wh kg −1 and 2.5 Wh kg −1 at power densities of 6700 W kg −1 and 14 000 W kg −1, respectively.